(untitled) (Dialogos, 2017)
O artigo pretende explorar uma nova hipótese para explicar o comportamento político da União Democrática Nacional (UDN), especialmente a congruência entre o pensamento “udenista” e os valores de parte da Instituição Militar. A assimilação da cultura política da elite política do Estado de Minas Gerais também contribuiu para forjar a identidade do udenismo. Abstract. The article intends to explore a new hypotesis in order to explain the political behavior of National Democratic Union(UDN), especially the consonance between the thought “udenista” and the values of part of the Military Institution. The assimilation of the political culture of the political elite